PSYCHOLOGICAL PECULIARITIES OF PROFESSIONAL BURNOUT AND RESILIENCE OF EMPLOYEES IN THE STATE EMERGENCY SERVICE OF UKRAINE - Nazarovets, Tetiana (Personality and environmental issues, 2024)
An important task of psychological science in the modern military confrontation of the state is to study the psychological characteristics of employees in the organs and units of the State Service of Ukraine for Emergencies (SES). Since they are the first to arrive at the scene of missile strikes, man-made disasters, ensure the protection of the population and territories from emergencies, etc. It is important to study those personal characteristics that help SES employees perform their professional tasks and prevent professional burnout in time.To determine the psychological characteristics, including signs of professional burnout and resilience, of employees in SES organs and units, a psychodiagnostic set of methods was compiled, which included the following: G. Schubert's Risk Readiness Inventory, R. Schwartz and M. Jerusalem's Self-Efficacy Scale, C. Spielberg's Reactive and Personal Anxiety Scale, A. T. Beck's Depression Scale, A. Bass and A. Darkey's Questionnaire, J. Greenberg's Burnout Syndrome Test, and the Resilience Scale.It was found that the vast majority of the subjects have low and medium levels of anxiety, which indicates the prevalence of their internal stability.In the study of the depressive states expirience, it was found that the majority of the subjects are in a normal state. However, a small number of subjects have indicators of depression that require psychocorrection.It has been found that the respondents did not show indicators of professional burnout and have a high level of resistance.According to the results of the empirical study, it was found that the most powerful in the personal structure of employees in the SES organs and units are resilience and professional burnout. The study also revealed powerful connections between depression and the least connected (i.e. isolated) were the indicators of the index of independence, reflexivity and self-acceptance.Negative relationships between professional burnout and balance and self-efficacy have been established, i.e., the higher the indicators of balance and self-efficacy, the lower the indicators of professional burnout.Positive relationships between professional burnout and depression and personal anxiety have been established, i.e., the higher the indicators of depression and anxiety, the higher the indicators of professional burnout.Accordingly, to reduce the risks of professional burnout, further psychocorrectional work should be aimed at reducing personal anxiety and depression, as well as increasing resilience, self-efficacy, and balance.